2014
DOI: 10.1016/j.neuroscience.2014.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Strain-dependent brain defects in mouse models of primary ciliary dyskinesia with mutations in Pcdp1 and Spef2

Abstract: Hydrocephalus is caused by the accumulation of cerebrospinal fluid in the cerebral ventricular system which results in an enlargement of the cranium due to increased intraventricular pressure. The increase in pressure within the brain typically results in sloughing of ciliated ependymal cells, loss of cortical grey matter, and increased gliosis. Congenital hydrocephalus is associated with several syndromes including primary ciliary dyskinesia (PCD), a rare, genetically heterogeneous, pediatric syndrome that re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 75 publications
(117 reference statements)
0
31
0
Order By: Relevance
“…Loss of Cfap221 in nm1054 mutant mice results in PCD characterized by hydrocephalus, male infertility and airway abnormalities due to ciliary dysfunction 20 , 23 , 37 , 38 . Although no strain-specific differences have been observed for the reproductive or respiratory phenotypes, the hydrocephalus is more severe on the B6 background than 129 despite defects in ependymal cilia-driven fluid flow on both backgrounds 23 . To identify gene expression differences that might influence susceptibility to severe hydrocephalus in nm1054 mice on the B6 and 129 backgrounds, we utilized a DNA microarray approach.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Loss of Cfap221 in nm1054 mutant mice results in PCD characterized by hydrocephalus, male infertility and airway abnormalities due to ciliary dysfunction 20 , 23 , 37 , 38 . Although no strain-specific differences have been observed for the reproductive or respiratory phenotypes, the hydrocephalus is more severe on the B6 background than 129 despite defects in ependymal cilia-driven fluid flow on both backgrounds 23 . To identify gene expression differences that might influence susceptibility to severe hydrocephalus in nm1054 mice on the B6 and 129 backgrounds, we utilized a DNA microarray approach.…”
Section: Resultsmentioning
confidence: 99%
“…We have demonstrated that congenic mouse models of PCD lacking ciliary proteins CFAP221, CFAP54 and SPEF2 all have a severe hydrocephalus on the C57BL6/J (B6) background but not on 129S6/SvEvTac (129) or a mixed (B6x129)F1 background 20 22 , indicating strain specificity in susceptibility to severe PCD-associated hydrocephalus. While there are defects in cilia-driven fluid flow on both backgrounds, ventricular dilatation and secondary damage to surrounding brain tissue are consistently more severe in mutants on the B6 background 23 . These findings are consistent with reports of severe hydrocephalus in other PCD models on the B6 background and an absence of severe hydrocephalus in models on the 129 background 16 .…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Therefore, another protein identified in the present study, SPEF2, was of interest. SPEF2 is predominantly expressed in ciliated tissues, including lung, trachea, testis and brain tissue (36)(37)(38). It is required for ciliary motility and spermatogenesis, and the loss of SPEF2 function was reported to result in severe spermatogenic defects (36).…”
Section: Discussionmentioning
confidence: 99%
“…9,32 Murine studies have shown that certain PCD strains develop M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 11 alterations in neuronal differentiation, microglial activation, and myelination. 33 Interestingly, hydrocephalus is not limited to disturbances of motile cilia, and is in fact often detected in patients with primary ciolipathies, such as orofacialdigital syndrome and Bardet-Biedl syndrome. This suggests that mutations hindering the normal ciliary function may indeed affect both motile and primary cilia.…”
Section: Comparison To Reference Rangesmentioning
confidence: 99%